STUDENTS’ ENGAGEMENT ON KAHOOT! GAME TO PRACTICE ENGLISH VOCABULARY FOR VOCATIONAL HIGH SCHOOL STUDENTS - Suci, Intan Dwi Permata (Journal of English Teaching and Learning, 2025)
This study aims to explore students’ emotional engagement in the use of Kahoot! game as a tool for English vocabulary practice at vocational high school. This research employed a qualitative approach combined with case study design to examine how game-based learning media such as Kahoot! affects students’ engagement in vocabulary learning. The data were collected through observations, questionnaires and interviews involving twenty-five students from the tenth graders majoring tata kecantikan (TK). The findings reveal that the use of Kahoot! game make students active to engage, help to develop English vocabulary and help to understand unfamiliar vocabulary. Moreover, students expressed positive feeling during learning process. This study provide insight into the potential of technology-based learning such as digital games can help students’ engagement to be active and develop their vocabulary skills. Furthermore, it offers recommendations for implementing interactive game in other materials to develop other skills in vocational high school contexts